2008
DOI: 10.1103/physreva.77.032331
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic information transport in the presence of decoherence

Abstract: We study adiabatic population transfer between discrete positions. Being closely related to STIRAP in optical systems, this transport is coherent and robust against variations of experimental parameters. Thanks to these properties the scheme is a promising candidate for transport of quantum information in quantum computing. We study the effects of spatially registered noise sources on the quantum transport and in particular model Markovian decoherence via non-local coupling to nearby quantum point contacts whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…In order to discuss the transfer of double excitation states, we make use of the wave function (8). Since for the transfer mediated by the atoms, the best result is expected to occur when the atomic transition frequencies are in resonance with the cavity field frequencies, we set ∆ = 0 in what follows in this section.…”
Section: A Transfer Mediated By Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to discuss the transfer of double excitation states, we make use of the wave function (8). Since for the transfer mediated by the atoms, the best result is expected to occur when the atomic transition frequencies are in resonance with the cavity field frequencies, we set ∆ = 0 in what follows in this section.…”
Section: A Transfer Mediated By Atomsmentioning
confidence: 99%
“…In most schemes, linear atomic chains or atomic (spin) lattices are considered for the transfer of quantum states [8][9][10]. In these models the transfer is mediated by the direct dipole-dipole coupling between neighbouring atoms, which induces the flow of an initial excitation through the chain [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, such measurement would influence the effect that it should substantiate. For example, coupling the middle dot to a charge detector [6,7] impacts significantly on the dot populations [8], since it causes decoherence to which CTAP is quite sensitive [9]. Consequently, as a matter of principle, direct observation of the dot populations is of limited use and, thus, one may have to resort to an indirect verification.In this work, we propose a generalization of CTAP that circumvents this difficulty and predicts an experimental fingerprint for the non-occupation of the middle dot.…”
mentioning
confidence: 99%
“…Increasing the transfer distance, we found that the effi- ciency of QST is inversely proportional to the distance of the two QDs. In a real system, decoherence is the main obstacle to the experimental implementation of quantum information [23,24]. There are two sources of quantum decoherence in QDs, one is due to charge dephasing brought by lead-QD coupling and the other is due to the hyperfine interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%